Cranial burr holes in the emergency department: to drill or not to drill?. Issue 3 (30th December 2019) - Howard, Alan; Krishnan, Vinaithan; Lane, Gerard; Caird, John
Abstract : The practice of trepanning (referred to today as a craniotomy) dates back to the Neolithic period. Reasons for drilling a hole through the skull evolved from releasing evil spirits and curing insanity to practical management of head injuries in ancient Greece and Rome. Today, craniotomy or drilling a burr hole through the skull is very much the purview of the neurosurgeon. Yet one could argue that the procedure itself is more 'bone surgery' than 'brain surgery'. Nevertheless, despite the fact that head injury is a common presentation at district general hospitals and traumatic extra-axial haemorrhages are encountered often, the straightforward skillset required to drill a burr hole as a pretransfer, temporising, life-saving measure is seldom taught and has never gained traction. What we advocate in this article is the adaptation and novel application of an old, tried and tested technique in new hands. The critical pathophysiological turning point of any expanding extra-axial haemorrhage is the inflection point on the volume/Intracranial pressure (ICP) curve beyond which compensation is impossible. The subsequent rising ICP initiates a predictable continuum of clinical signs signalling progressive herniation. There are few emergencies as time-critical as a patient with an isolated, expanding extradural haemorrhage embarking on a trajectory of rostrocaudal deterioration and inevitable death. In many cases, the tragedy is compounded by the knowledge that such a patient probably has a healthy underlying brain, often evidenced by a lucid period after trauma. Our emergency department is attached to a small 300-bed District General Hospital (DGH) on the rural North West coast of Ireland. We are 262 km distant by road from a national neurosciences department that can, at best, be reached in 2 hours and 30 min. Quality improvement review of years of dismal outcomes in patients such as those described earlier with potentially remediable pathology prompted research and development of the skillset we are now able to offer, an old technique in new hands.